Case Writing: Learning through Constructive Reflection - Rosemary B. Closson; Carmeda Stokes (Adult Education Research Conference, 2008)
Abstract: Case-based and problem-based learning are seldom discussed in regard to their use in adult education practitioner preparation. Here researchers discuss a process called “case construction” as a means for master’s students to learn effective management principles.
Keywords: case-based teaching; reflection; experiential learning